Effect of Green Marketing on Sustainable Business Development - Acharya, Ghanashyam (Nepalese Journal of Management, 2025)
This study examines the effect of green marketing on sustainable business development. Environment Sustainability is the dependent variable. The selected independent variables are green products, green prices, green promotion, green packaging, and Eco labels. The primary source of data is used to assess the opinions of respondents regarding green products, green prices, green promotion, green packaging, eco labels and environment sustainability. The study is based on the primary data of 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of green marketing on sustainable business development in the context of Kathmandu valley. The study showed that green products have a positive effect on environmental sustainability indicating that green products lead to increase environmental sustainability. Likewise, green price has a positive effect on environmental sustainability. This implies that improvement in green prices leads to the increase in sustainability of the product. Similarly, green promotion has a positive effect on environment sustainability. It indicates that better the green promotion better will be the customer understanding about the product. However, green packaging has a positive effect on the environmental sustainability that leads to the increment of performance. Moreover, eco labels have a positive effect on environmental sustainability that indicates that betterment in products leads to the betterment in sustainability.